Examining the moderating role of religiosity on taxpayer awareness, digital tax services, and taxpayer compliance - Bayu Adi; Siti Istikhoroh (AFRE (Accounting and Financial Review), 2026)
This study examines the influence of taxpayer awareness and tax service digitalization on taxpayer compliance and investigates the moderating role of religiosity. A total of 100 respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine relationships among the study variables. The findings indicate that taxpayer awareness positively affects taxpayer compliance, suggesting that individuals with greater awareness of their tax obligations tend to demonstrate higher compliance. Tax service digitalization was also found to positively influence taxpayer compliance, indicating that accessible and efficient digital tax services support compliance behavior. Religiosity strengthened the relationship between taxpayer awareness and compliance, suggesting that religious values reinforce the influence of awareness on taxpayers’ decisions to comply. However, religiosity did not moderate the relationship between tax service digitalization and compliance. One possible explanation is that, where digital tax services have become routine administrative mechanisms, their effectiveness may depend more on technological and service-related factors than on religious values. This study contributes to the tax compliance literature by integrating behavioral, technological, and moral perspectives within a single framework. The findings also highlight the importance of combining taxpayer education initiatives with accessible and high-quality digital tax services to support voluntary taxpayer compliance.